Erratum: Notes on the type specimen of Acanthocalyx delavayi (Caprifoliaceae) at Herbarium of the National Museum of Natural History in Paris (P) - Mu, Qi-Yong; Yu, Chih-Chieh; Xing, Yao-Wu (Phytotaxa, 2020)
N/A